Pengembangan Strategi Pemasaran Digital guna Meningkatkan Eskposur UMKM Winny Skincare Batam - Delfina, Delfina; Candy, Candy (Lembaga Dongan Dosen, 2023)
Winny Skincare Batam is an MSME that has been running its business online for 3 years in distributing local skincare. During operation, this MSMEs only use Facebook for marketing, namely through the live feature. Based on interviews that have been conducted, it is known that MSME owners do not understand the use of marketing which is currently popular. MSME owners have tried using Instagram but were confused about the content to upload. Apart from that, when using Shopee, MSME owners also have difficulty registering their shop. Therefore, the dedication was carried out to help Winny Skincare Batam increase its business exposure by developing more optimal marketing strategies, as well as providing education to MSME owners regarding digital marketing. The results of this service are in the form of Instagram content designs, business logos, business cards, Linktree, and Shopee accounts which can be used in the long term by MSME owners. In implementing marketing strategies via Instagram, statistics show positive results after uploading all designed content. Likewise, statistics on Linktree show an increase in the number of clicks and visits from the audience. That way, Winny Skincare Batam will be known more widely from new media other than Facebook